2011
DOI: 10.1177/0265378810396299
|View full text |Cite
|
Sign up to set email alerts
|

The Visibility of Mission Agencies in General and USPG in Particular Among Recently Ordained Anglican Clergy: An Empirical Enquiry

Abstract: Attitudes toward mission agencies in general, and toward the United Society for the Propagation of the Gospel (USPG) in particular, were assessed using two 10-item scales completed by 833 recently ordained Anglican clergy from the UK. Clergy were generally positive toward mission agencies, willing for their churches to engage with them, but more reluctant to form personal links. Most clergy felt agencies should give priority to the relief of poverty and to development needs, rather than on spreading specifical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The results reported here are based on two separate studies, one on laity carried out from 2000 to 2002 and extensively reported elsewhere (Village 2005a(Village , 2005b(Village , 2005c(Village , 2006(Village , 2007Village and Francis 2005) and one on clergy from 2004 to 2007 that has been reported on briefly elsewhere (Village, 2011). The study on laity was based on 404 responses from 11 congregations that spanned the three main traditions within the Church of England.…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…The results reported here are based on two separate studies, one on laity carried out from 2000 to 2002 and extensively reported elsewhere (Village 2005a(Village , 2005b(Village , 2005c(Village , 2006(Village , 2007Village and Francis 2005) and one on clergy from 2004 to 2007 that has been reported on briefly elsewhere (Village, 2011). The study on laity was based on 404 responses from 11 congregations that spanned the three main traditions within the Church of England.…”
Section: Methodsmentioning
confidence: 95%
“…In both cases it was difficult to tell how far these were representative of the church as a whole, but the evidence from age and sex distributions suggested they were a reasonable cross section of the Anglican Church in England. (For details of the samples and how they relate to the wider church, see Village (2007) and Village and Francis (2011)). The lay sample probably over-sampled those who read the Bible frequently and attended church often, but this section of the laity is the one for whom the issues in this study are most pertinent.…”
Section: Methodsmentioning
confidence: 99%